Evaluation of half-sib progenies and their parents of Populus euphratica based on their morphologic and micro-morphologic traits - Masoumeh Homaie; Hossein Mirzaie Nodoushan; Fereshteh Asadi Corom; Gholamreza Bakhshi Khaniki; Mohsen Kalagari (تحقیقات جنگل و صنوبر ایران, 2014)
Populus euphratica Oliv. is one of the important poplar species which regenerate mainly through asexual reproduction, for which there is not enough genetic variation within its plant populations. This work investigated several morphological and micro-morphological traits on four half-sib progenies of each eleven parental clones of the species which was grown in a collection at Alborz Research Station, located at Karaj, Iran, as new produced genotypes. Therefore, 44 new clones of progenies of 11 parental clones were studied, based on a nested statistical model for the traits. Results indicated a vast variation between the studied parents and their progenies that may be used to produce new commercial varieties of the species. Average performance of the studied progenies increased on the traits such as leaf length and width, of which leaf area would be increased; resultantly this would improve plant photosynthesis. The higher performances of the progenies for the traits imply a suitable potential for selecting the genotypes with higher performance within the new produced progenies. Petiole length and leaf width showed a significant positive correlation to stomata length as well as significant negative correlation to number of stomata. Regarding the role of stomata on plant photosynthesis, the correlation values may be used for indirect selection of suitable genotypes of the species.